Assessment of adjustment disorder in people with COVID-19 infection - PEKER, MEHMET SERTAÇ; TOPUZOĞLU, AHMET (My University, 2023)
Objective: This study aimed to evaluate the development of adjustment disorder according to the ADNM-20 (Adjustment Disorder New Module-20) scale in participants who were followed up for Covid-19 infection. Methods: A cross-sectional survey was conducted from September to November 2020. After sample size calculation, we aimed to reach minimum 170 people out of 1290 people who applied to the hospital for Covid-19 disease treatment. Participants were selected from the patients admitted to the hospital using a simple stratified random sampling method. We reached 182 people after treating the patients who were followed up with Covid-19 infection in a University Hospital in Istanbul, Turkey. A questionnaire and the Adjustment Disorder New Module-20 scale were applied via phone / mail at the end of the 6th month after Covid-19 related hospital admission by researchers. Results: Adjustment disorder was found in 28.8 % (n=42) of the participants disorder according to the ADNM-20 scale. While the rate of development of adjustment disorder due to Covid-19-related stress was 26.7 % (n=39); the rate of development of adjustment disorder due to non-Covid-19 stress was found to be 2.1 % (n=3). With the increase in stress load, the development of adjustment disorder increased significantly. The frequency of developing Covid-19-related stress-related adjustment disorder was statistically significantly increased with the duration of exposure to stress. Conclusion: We have found out that one out of every four people who apply to the hospital for healthcare services due to Covid-19 infection may develop an adjustment disorder. Assessment of the adjustment disorder more frequently and making early interventions may contribute to the prevention of progressive mental disorders.

Amaç: Bu araştırmada, uyum bozukluğu değerlendirme ölçeğine göre (ADNM-20); Covid-19 enfeksiyonu nedeniyle takip edilmiş hastalarda uyum bozukluğu gelişimini değerlendirmek amaçlandı. Yöntem: Kesitsel tipteki araştırma Eylül- Kasım 2020 tarihleri arasında gerçekleştirildi. Hastaneye başvuran 1290 kişiden 170 kişiye ulaşılması hedeflendi. Bu süreçte hastaneye başvuran hastalardan tabakalı basit rasgele örnekleme yöntemi ile katılımcılar seçildi. Covid-19 enfeksiyonu nedeniyle İstanbul’da bir üniversite hastanesinde takip edilmiş tedavi edilen 182 kişiye ulaşıldı. Covid-19 ile nedeniyle takip edilen hastalara; hastaneye yatıştan sonraki 6. ayın sonunda telefon/posta yoluyla sosyodemografik sorular ve Uyum Bozukluğu Yeni Modül-20 ölçeğinden oluşan bir anket uygulandı. Bulgular: Katılımcıların % 28.8’inde (n=42) uyum bozukluğu saptandı. Covid-19 ilişkili strese bağlı uyum bozukluğu gelişen katılımcılar %26.7 (n=39) iken; Covid-19 dışı stres nedenli uyum bozukluğu gelişme oranı %2.1 (n=3) bulundu. Stres yükü artışıyla uyum bozukluğu gelişimi istatistiksel olarak anlamlı şekilde artıyordu. Artan strese maruz kalma süresi ile Covid-19 ilişkili strese bağlı uyum bozukluğu gelişme sıklığı istatistiksel olarak anlamlı olarak artmaktaydı. Sonuç: Covid-19 nedeniyle sağlık hizmeti almak için hastaneye başvuran her dört kişiden birinde uyum bozukluğu gelişebilmektedir. Uyum bozukluğunun daha fazla sorgulanarak erken müdahalelerde bulunulması ilerleyici ruhsal bozuklukların önlenmesine katkıda bulunabilir.
COVID-19 enfeksiyonu geçiren bireylerde uyum bozukluğu değerlendirilmesi
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Sağlık Politikaları; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Health Policy; Public Health, Environmental and Occupational Health; Epidemiology; Adjustment Disorder; Covid-19; Mental Health; Covid-19; Uyum Bozukluğu; Ruh Sağlığı; Covid-19; Adjustment Disorder; Mental Health